Selective Packaging in Murine Coronavirus Promotes Virulence by Limiting Type I Interferon Responses - Jeremiah Athmer (American Society for Microbiology, 2018)
ABSTRACT Selective packaging is a mechanism used by multiple virus families to specifically incorporate genomic RNA (gRNA) into virions and exclude other types of RNA. Lineage A betacoronaviruses incorporate a 95-bp stem-loop structure, the packaging signal (PS), into the nsp15 locus of ORF1b that is both necessary and sufficient for the packaging of RNAs. However, unlike other viral PSs, where mutations generally resulted in viral replication defects, mutation of the coronavirus (CoV) PS results in large increases in subgenomic RNA packaging with minimal effects on gRNA packaging in vitro and on viral titers. Here, we show that selective packaging is also required for viral evasion of the innate immune response and optimal pathogenicity. We engineered two distinct PS mutants in two different strains of murine hepatitis virus (MHV) that packaged increased levels of subgenomic RNAs, negative-sense genomic RNA, and even cellular RNAs. All PS mutant viruses replicated normally in vitro but caused dramatically reduced lethality and weight loss in vivo. PS mutant virus infection of bone marrow-derived macrophages resulted in increased interferon (IFN) production, indicating that the innate immune system limited the replication and/or pathogenesis of PS mutant viruses in vivo. PS mutant viruses remained attenuated in MAVS−/− and Toll-like receptor 7-knockout (TLR7−/−) mice, two well-known RNA sensors for CoVs, but virulence was restored in interferon alpha/beta receptor-knockout (IFNAR−/−) mice or in MAVS−/− mice treated with IFNAR-blocking antibodies. Together, these data indicate that coronaviruses promote virulence by utilizing selective packaging to avoid innate immune detection. IMPORTANCE Coronaviruses (CoVs) produce many types of RNA molecules during their replication cycle, including both positive- and negative-sense genomic and subgenomic RNAs. Despite this, coronaviruses selectively package only positive-sense genomic RNA into their virions. Why CoVs selectively package their genomic RNA is not clear, as disruption of the packaging signal in MHV, which leads to loss of selective packaging, does not affect genomic RNA packaging or virus replication in cultured cells. This contrasts with other viruses, where disruption of selective packaging generally leads to altered replication. Here, we demonstrate that in the absence of selective packaging, the virulence of MHV was significantly reduced. Importantly, virulence was restored in the absence of interferon signaling, indicating that selective packaging is a mechanism used by CoVs to escape innate immune detection.